PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN AGROWISATA DAN DAMPAKNYA TERHADAP SOSIAL EKONOMI MASYARAKAT (Studi Kasus pada Agrowisata Kampung Flory, Sleman, Yogyakarta) - Zaqiah Ramdani; Tuti Karyani (Universitas Galuh Ciamis, 2020)
Sleman Regency, Yogyakarta has a tourism potential that is a destination for local and foreign tourists. Kampung Flory is one of the attractions in Sleman Regency that carries the concept of back to nature and community-based tourism (CBT). The study was conducted aiming to determine the participation of the community involved in the development of Kampung Flory and its impact on the socio-economic conditions of the community. This research uses a qualitative approach with case study. Determination of the research subject purposively and the data were analyzed through methods of observation, interviews, literature study, documentation, and likert scale. The analysis showed that community participation in the planning and evaluation stages was in the moderate or good category, as for the stages of implementation and utilization of the results it has been very good, it's just that in the communities involved there are still not many, so it is necessary to optimize the human resources involved. The socio-economic impacts felt by the people of Kampung Flory include being able to work together with fellow citizens by working together, being able to increase knowledge and knowledge, being able to increase income, and being able to create jobs so as to reduce unemployment and poverty.